Regionalism in tourism - the case for Kenya and Ethiopia - Frost, Frederick; Shanka, Tekle (Routledge, 2001)
Africa represents a continent of almost infinite tourism potential and yet it lags far behind the rest of the world as a tourist opportunity. There are clearly pockets of excellence, countries that have, and are achieving significant tourism outcomes. However, these are the mi-nority-what of the remainder? In this paper a single regional coupling is proposed between two countries that appear on the surface to be ill matched. Closer inspection reveals that the senior partner in capitalizing on tourism development, Kenya, is in need of revitalization whilst the junior partner, Ethiopia, has great potential that is yet to be capitalized on. They share a significant geographical feature-the Rift Valley-and both have substantial assets in terms of flora and fauna. Ethiopia, regarded as the cradle of human origin, has substantial historical attractions, exemplified by the Historic Route. In this paper, elements of the need for, and, benefits of collaboration are outlined. This modest approach to regionalism in terms of tourism, could become, if successful, a model for other regional activities in the continent. Africa and specifically sub-Saharan Africa represents a range of exciting tourism opportunities by many standards. In terms of product, whether it is the flora or fauna, or locations, it would appear to be a tourism marketer’s dream. Unfortunately its true potential in terms of tourism has not been realized. At tourism conference after tourism conference, this part of the world is seen to be the “Orphan Annie” of tourism. This situation is re-flected in the majority of comparative tourism statistics. Whilst numerous authors have identified reasons for this, solutions are more difficult to develop. In this paper, the concept of regionalism as a possible solution is developed in terms of two adjoining sub-Saharan countries, Kenya and Ethiopia. © 2002, Taylor & Francis Group, LLC. All rights reserved.